Smanjvanje istosmjerne komponente struje izmjenjivača s galvanskim odvajanjem na tračničkim vozilima : doktorski rad - Macan, Miroslav; Jakopović, Željko (Zagreb: M. Macan ; Fakultet elektrotehnike i računarstva, 2015)
Istraživanja prikazana u ovome radu motivirana su problemima vezanim uz klasične metode određivanja i smanjenja zasićenja u transformatorima. Za uspješno projektiranje pretvarača pomoćnih napajanja s galvanskim odvajanjem za napon istosmjernog međukruga 1500 V ili 3000 V potrebno je ograničiti istosmjernu komponentu struje na izlazima izmjenjivača. Uobičajene metode za određivanje istosmjerne komponente struje predviđaju dodatne mjerne članove magnetskog toka, što znatno usložnjava i poskupljuje izvedbu pretvarača, pa je cilj bio razviti metodologiju određivanja istosmjerne komponente struje bez dodatnih mjerenja s ocjenom granica točnosti.
Istražen je utjecaj parametara IGBT sklopke i pobudnog stupnja na iznos istosmjerne komponente napona na izlazima izmjenjivača. Kao rezultat istraživanja izrađen je algoritam potiskivanja istosmjerne komponente struje. Algoritam se temelji na metodi promjene srednje vrijednosti modulacijske funkcije. Na osnovi trenutačne vrijednosti istosmjerne komponente struje kompenzirana je srednja vrijednost napona na izlazima izmjenjivača.
Prednost predloženog algoritma za potiskivanje istosmjerne komponente struje u odnosu na većinu postojećih metoda jest jednostavno i pouzdano upravljanje minimalnom istosmjernom komponentom struje na izlazima izmjenjivača za cijeli opseg promjene izlaznog napona i za cijeli opseg opterećenja. U radu je prikazano da predložena metoda vrlo dobro pokazuje rezultate smanjenja istosmjerne komponente struje izmjenjivača s galvanskim odvajanjem na tračničkim vozilima.

Ključne riječi:    PWM izmjenjivač, IGBT sklopka, pobudni stupanj, mrtvo vrijeme, istosmjerna komponenta struje
Over the past twenty years a large number of auxiliary power converters with galvanic isolation for use in railway application have been investigated. Different solutions, which differ primarily by the fact that the power supply contact lines are intended, have been used.
Auxiliary power supply for modern railway vehicles, powered from the DC catenary line with nominal voltage of 1500 V or 3000 V, as well as in case of AC supply with DC-link voltage more than 1000 V, is realized with a three-phase inverter, and a three-phase transformer. On the input side the inverter is connected via input filter to DC catenary line or directly to DC-link of propulsion converter, while on the output side, a three-phase transformer is connected to inverter
Transformer is used for galvanic isolation of the pulse width modulated DC-link voltage, and the on-board power supply. Galvanic isolated inverters are built with arrangements of semiconductor switches which provide AC excitation to a transformer. Ideal AC power sources do not include DC component. However, at some instances inverter include DC component in its output voltage. Phenomena such as unmatched turn-on/turn-off times, semiconductor forward voltage drop, gate driving signal delays or pulsating load, among others, can cause differences in the positive and negative volts-seconds applied to the transformer. This results in a DC voltage component at the transformer terminals, which causes an undesired DC magnetic flux density component in the transformer core, distorted output voltage, and acoustic noise are the result when the component is large enough.
For successful design of galvanically separated auxiliary power supply it is necessary to limit DC current component at the inverter outputs. Which method will be selected depends on the used control system, on the characteristics of IGBT switches, and IGBT drivers, economic conditions as well as the experience, and preferences of the designers. Data concerning the maximum allowed DC current is one of the designer data upon which are defined the requirements for inverter, and control circuit. Likewise, when inverter is selected, the information regarding the maximum inverter DC current is an essential designer data which enables an appropriate transformer choice.
With passive methods no current sensor and complex control are required but system results with the larger sizes of transformers. On the other hand, active methods have a practical limitation because of the high complexity of control structure. Therefore, benefits of comparison are limited. Common active methods of determining DC current component foresee additional magnetic flux measuring sensors which significantly increase complexity and manufacturing cost of the inverter so the goal was to develop a methodology capable of determining DC current component with no additional measurements while retaining evaluation of accuracy limits. Therefore, researches in this thesis are motivated with issues connected to classical methods of detecting and preventing method for magnetic field saturation of transformers.
The influence of the parameters of IGBT switch and IGBT driver on output inverter DC voltage component is analyzed. As a result of investigation activities was found minimisation algorithm of DC current component. Algorithm is based on the modification method of the average value of modulation functions. Based on the instantaneous value of the DC current component, inverter output average voltage value was compensated.
The advantages of the proposed minimisation algorithm of DC current component, compared to the existing methods, are simple and reliable converter control, with minimal DC current component at the inverter outputs provided for the whole range of the output voltage and the load. The conclusion is that the proposed method shows very good effects of minimisation of DC current component in galvanic isolated inverters for railway applications

Key words:    PWM inverter, IGBT switch, IGBT driver, dead time, DC current component
Bibliografija str. 178-182.